Academic performance of university students in the Dominican Republic during the COVID-19 pandemic: Temporal analysis (Innovaciones Educativas, 2023)
Academic performance in higher education refers to the performance and achievement attained by students, including aspects such as grades, averages and self-regulation processes assumed by the student. The study of academic performance is crucial to evaluate the progress and promote the educational success of students, which facilitates personal and institutional development, so the aim is to analyze the impact of COVID-19 on the academic performance of students at the Universidad Católica del Cibao in the Dominican Republic. For this purpose, the longitudinal method was used, which made it possible to analyze and understand the changes and trends over the course of five academic periods. The results indicate that the pandemic has had a positive impact on the academic performance of university students. It was observed that students who use self-regulated learning strategies, such as setting clear goals, the use of planning strategies and time organization have achieved better results. In conclusion, the results obtained highlight that academic performance is associated to a greater mastery of self-regulation activities, to the student's skills and to the teacher's support. It also highlights the importance of self-regulation of learning and the need to implement effective strategies to close the learning gap that has emerged during this period. These findings are valuable for the scientific community and may contribute to the design of policies and measures to promote optimal academic performance in similar situations in the future.
Keywords: academic performance; virtual education; pandemic; higher education; self-regulation